Factionalism in the French Parti Socialiste, 1971-1981 - Cole, A; Cole, Alistair M. (1985)
﻿ This thesis concentrates on the cause, structure, location and context (rather than the function) of factions within the French Parti Socialiste, from the Congress of Epinay, in June 1971, until Mitterrand's election as Socialist President of the Republic, on May 10th, 1981. It argues that factionalism results from a complex, interrelated cleavage structure: groups are differentiated according to a number of salient variables, of which the most important are personality (accentuated by the presidentialised Fifth Republic); ideology/policy; strategy/tactics; organisational interests and different historical origins. Factional relations are a product both of the intra-party consequences of the party's external objectives, and the internal dynamic created by factional competition itself. The party is thus an evolutive, rather than a static entity. [continued in text ...]